Prediction of tribocorrosion processes in titanium-based dental implants using acoustic emission technique: Initial outcome - Barão, Valentim A.R. (2021)
The use of dental implants is growing rapidly for the last few decades and Ti-based dental implants are a commonly used prosthetic structure in dentistry. Recently, the combined effect of corrosion and wear, called tribocorrosion, is considered as a major driving process in the early failure of dental implants. However, no previous study has reported the prediction of tribocorrosion processes in advance. Therefore, this study is a novel investigation on how the acoustic emission (AE) technique can predict tribocorrosion processes in commercially-pure titanium (cpTi) and titanium-zirconium (TiZr) alloys. In this study, tribocorrosion tests were performed under potentiostatic conditions and AE detection system associated with it captures AE data. Current evolution and friction coefficient data obtained from the potentiostatic evaluations were compared with AE absolute energy showcased the same data interpretation of tribocorrosion characteristics. Other AE data such as duration, count, and amplitude, matched more closely with other potentiostatic corrosion evaluations and delivered more promising results in the detection of tribocorrosion. Hence, AE can be consider as a tool for predicting tribocorrosion in dental implants. Experimental results also reveal Ti5Zr as one of the most appropriate dental implant materials while exposing Ti10Zr's lower effectiveness to withstand in the simulated oral environment.